<Methods for estimating body weight and height in hospitalized adults: a comparative analysis> - Ana Paula Ferreira Melo; Raquel Kuerten de Salles; Francilene Gracieli Kunradi Vieira; Marilyn Gonçalves Ferreira (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to compare the values obtained through methods directed to height and body weight estimates in relation to measurements taken from hospitalized adult. Study participants were 142 adults of both genders. Anthropometric measurements of body weight, height, knee height, arm length, span, demi-span, recumbent height, calf, arm and abdominal circumferences and subscapular skinfold thickness were taken. The actual measurements were compared with those obtained from formulas for estimating weight and height, using the paired t test. The estimated measurements differed significantly (p <0.001) from the actual measurements in both genders, observing the tendency of overestimating these measurements. The exception was the estimated height for men by the formula that utilizes the variable knee height (p> 0.001). The average estimated body weight closest to the actual body weight for men was obtained with the formula that used the measurements of arm, abdominal and calf circumferences. For women, the biggest coincidences were obtained by means of the formula that utilizes the variable knee height. For both men and women, the averages related to the body mass index, calculated through estimated body weight and height measurements resulted in the same nutritional diagnosis when compared to the body mass index involving actual measurements. The estimated height by the formula that utilizes the variable knee height among men was the only measurement which did not represent significant differences. Other methodologies for estimating body weight and height presented significant differences, which suggests that new studies using other methodologies are necessary.